2021
DOI: 10.1183/13993003.00116-2021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary embolism in patients with COVID-19 at the time of hospital admission

Abstract: A high prevalence of venous thromboembolism (VTE) has been reported during Intensive Care Unit (ICU) hospitalisation in patients with severe coronavirus disease (COVID-19) [1, 2]. In most cases, the diagnosis of pulmonary embolism (PE) was incidental as patients underwent computed tomography pulmonary angiography (CTPA) for aggravation of their respiratory condition. Higher mortality is also described in patients with high D-Dimer levels suggesting that VTE complication may contribute to unfavourable prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 12 publications
(12 reference statements)
3
41
1
4
Order By: Relevance
“…In the Netherlands, thromboembolic complications were reported in 57 of 184 (31%) patients with COVID-19 ARDS and treated in ICU, and the lung was the most common localization of thromboembolism (25%) (5). In a French study, in which all consecutive patients with COVID-19 performed CTPA at admission, PE was diagnosed in 14.2% of the patients (14). Our cohort had a higher frequency of PE than another study that also reported a lower incidence of ICU admissions, suggesting that fewer patients were critically ill (15).…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, thromboembolic complications were reported in 57 of 184 (31%) patients with COVID-19 ARDS and treated in ICU, and the lung was the most common localization of thromboembolism (25%) (5). In a French study, in which all consecutive patients with COVID-19 performed CTPA at admission, PE was diagnosed in 14.2% of the patients (14). Our cohort had a higher frequency of PE than another study that also reported a lower incidence of ICU admissions, suggesting that fewer patients were critically ill (15).…”
Section: Discussionmentioning
confidence: 99%
“… Ackermann et al, 2020 , Bunce et al, 2011 , Ceriani et al, 2010 , Chen et al, 2020 , Chi et al, 2020 , Choi et al, 2020 , Connors and Levy, 2020 , Egger et al, 2011 , Fauvel et al, 2020 , Alonso-Fernández et al, 2020 , Flumignan et al, 2020 , Fox et al, 2020 , Gervaise et al, 2020 , Gupta and Madhavan, 2020 , Hajra et al, 2020 , Jalaber et al, 2020 , Jevnikar et al, 2020 , Jiménez et al, 2020 , Higgins et al, 2003 , Ameri et al, 2020 , Huisman et al, 2018 , Kim et al, 2007 , Kirsch et al, 2020 , Konstantinides et al, 2019 , Kosior et al, 2020 , Kunutsor and Laukkanen, 2020 , Lax et al, 2020 , Liao et al, 2020 , Llitjos et al, 2020 , Artifoni et al, 2020 , Mestre-Gómez et al, 2020 , Mouhat et al, 2020 , Mueller-Peltzer et al, 2020 , Nopp et al, 2020 , Ooi et al, 2020 , Pandey and Agarwal, 2020 , Planquette et al, 2021 , Rodriguez-Sevilla et al, 2020 , Poyiadji et al, 2020 , Salje et al, 2020 , Bavaro et al, 2020 , ShiL et al, 2020 , Soumagne et al, 2020 , Soumagne et al, 2020 , Sungnak et al, 2020 , van Dam et al, 2020 , Varga et al, 2020 , Ventura-Diaz et al, 2020 , Watchmaker et al, 2020 , Worldometer COVID-19 Data 2020 , Wu et al, 2020 , Zeng et al, 2015 , Zheng et al, 2020 , Bilaloglu et al, 2020 , BujaL et al, 2020…”
Section: Uncited Referencesmentioning
confidence: 99%
“…We read with interest the research letter recently published by Jevnikar et al about the prevalence of pulmonary embolism (PE) in patients with coronavirus disease (COVID-19) at the time of hospital admission [1]. In this prospective multicenter study, all consecutive adult outpatients that were hospitalised with a diagnosis of COVID-19 in three tertiary French hospitals between April 15 th and May 23 rd 2020 underwent computed tomography pulmonary angiography (CTPA).…”
Section: To the Editormentioning
confidence: 99%